Effects of Myrtle (Myrtus communis L.) Fruit Cold Storage Under Modified Atmosphere on Liqueur Quality. Issue 1 (10th May 2016) - Fadda, Angela; Palma, Amedeo; D'Aquino, Salvatore; Mulas, Maurizio
Abstract: Myrtle berries were stored for 30 days at 2C in air (control) or O2 at 60 or 80% with the aim to extend the liqueur processing season. Oxygen treated berries had a lower pH and titratable acidity than control. No treatment effect was observed on weight loss and respiration rate. CIELAB coordinates demonstrated a darkening of the oxygen treated fruit. Hydro‐alcoholic extracts (HAE) from berries stored for 30 days at 80% O2 were less red colored than other treatments. After 10 and 20 days of storage, fruit held at 80% O2 had significantly higher total phenols than other treatments. Total anthocyanins increased with storage in all treatments. In the first 20 days of storage high oxygen treated berries showed higher anthocyanin content than control, whereas no difference among treatments were observed at 30 days. No differences were observed for the anthocyanin content in the HAE. Pratical Applications: The extension of the myrtle liqueur processing season is a major need for liqueur industries. In this article, the application, on myrtle berries, of postharvest storage in association with high oxygen treatments, proved to be useful to delay the processing time and, at the same time, to provide the liqueur industries of myrtle berries with good quality traits. The most important quality attributes for myrtle berries destined to transformation are the phenolic compounds in particular anthocyanins. Oxygen treatments have been successfully used for other commodities to improve the quality traits related to phenolic content. The results of this study will benefit the transformation industries in order to delay the processing season and to standardize the liqueur production. Furthermore it will add new data on the postharvest performances of small fruits.